DEVELOPING READING SKILLS AND STRATEGIES AT ADVANCED LEVEL (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
The article mentions the significance of the use of new pedagogical technologies in  teaching  reading strategies at advanced level and some problems related to improving reading skills are solved by  some practical solutions. All abilities,facilities and skills are analyzed  for how to be  advanced level readers.